2015
DOI: 10.1101/gr.191247.115
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced translocations arise from diverse mutational mechanisms including chromothripsis

Abstract: Unbalanced translocations are a relatively common type of copy number variation and a major contributor to neurodevelopmental disorders. We analyzed the breakpoints of 57 unique unbalanced translocations to investigate the mechanisms of how they form. Fifty-one are simple unbalanced translocations between two different chromosome ends, and six rearrangements have more than three breakpoints involving two to five chromosomes. Sequencing 37 breakpoint junctions revealed that simple translocations have between 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 68 publications
6
77
0
Order By: Relevance
“…Deletions and duplications mediated by HERV–HERV recombination at three intrachromosomal loci were sequenced in a recent study [43]. Similarly to other HERV-mediated chromosome rearrangements [4446], all the CNVs are flanked by HERV-H elements that are at least 3 kb in length and 93–96% identical. The longer length and significant sequence identity of intact HERV-H elements may make them particularly recombinogenic.…”
Section: Simple Intrachromosomal Svmentioning
confidence: 99%
See 3 more Smart Citations
“…Deletions and duplications mediated by HERV–HERV recombination at three intrachromosomal loci were sequenced in a recent study [43]. Similarly to other HERV-mediated chromosome rearrangements [4446], all the CNVs are flanked by HERV-H elements that are at least 3 kb in length and 93–96% identical. The longer length and significant sequence identity of intact HERV-H elements may make them particularly recombinogenic.…”
Section: Simple Intrachromosomal Svmentioning
confidence: 99%
“…Two recent studies of unbalanced translocations reported different types of DNA repair at junctions [45,46]. Sequencing the junctions of 37 unbalanced translocations revealed that 34 lacked extensive sequence homology [46].…”
Section: Simple Interchromosomal Svmentioning
confidence: 99%
See 2 more Smart Citations
“…Unless breakpoints disrupt important developmental genes, balanced translocations do not affect phenotype [15]. However, during gamete formation such chromosomes may segregate in unbalanced manner or unbalanced translocations may occur de novo and lead to monosomy and trisomy of different chromosome segments [16], which account for approximately 1% of developmental delay and intellectual disability cases in human [17][18][19]. Robertsonian translocations are a type of SVs resulting from chromosome end breaks near centromeric regions of two acrocentric chromosomes and their reciprocal exchange, which results in one large metacentric chromosome and one very small chromosome that is usually lost without phenotype effect.…”
Section: Structural Variationsmentioning
confidence: 99%